A simplified technique for custom made overdenture semi-precision attachments - Rajani A Dable; Bhushan S Gaikwad; Saurabh S Marathe; Mayura S Badgujar; Vinay R Dole (Wolters Kluwer Medknow Publications, 2013)
Context: Overdentures are the choice of treatment for most of them, but the only snag is its cost. In India, the rural areas are still deprived of quality treatment. This manuscript is showcasing a study, which is a cheaper, but effective way to provide the best to the patient. Aims: The aim of this study was to develop a custom made system, which can be used as an alternative treatment for the management of patients who need overdentures. The primary objective of this study was to provide a cost-effective attachment with the best functional efficacy. Materials and Methods: The semi-precision attachments were made by using the conventional technique of preparation of post space. The patterns were prepared by using the pattern resin material and the rest of the male and female attachments were fabricated by using innovative methods fulfilling the criteria. Results: The attachments were successfully used in patients with remarkably good function and comfort. Conclusion: It was a successful attempt to provide the specialized treatment in affordable cost. There is a need of innovative work to make the sophisticated systems more economical and readily available.